2015
DOI: 10.1007/s10826-015-0309-1
|View full text |Cite
|
Sign up to set email alerts
|

Does Mother–Child Interaction Mediate the Relation Between Maternal Depressive Symptoms and Children’s Mental Health Problems?

Abstract: The relation between maternal depressive symptoms and children’s mental health problems has been well established. However, prior studies have predominantly focused on maternal reports of children’s mental health problems and on parenting behavior, as a broad and unilateral concept. This cross-sectional study examined specific observed mother–child interaction behaviors through which maternal depressive symptoms are assumed to affect children’s mental health problems. We expected higher rates of maternal depre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
24
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 66 publications
6
24
0
4
Order By: Relevance
“…adolescent internalizing symptoms (van Doorn et al, 2016). One possible reason for this finding may be that mother-adolescent interaction behavior is more likely to influence immediate, shortterm emotions in mothers or adolescents.…”
Section: Empirical Discussion: the Mediating Role Of Mother-adolescenmentioning
confidence: 98%
See 3 more Smart Citations
“…adolescent internalizing symptoms (van Doorn et al, 2016). One possible reason for this finding may be that mother-adolescent interaction behavior is more likely to influence immediate, shortterm emotions in mothers or adolescents.…”
Section: Empirical Discussion: the Mediating Role Of Mother-adolescenmentioning
confidence: 98%
“…A carefully constructed and justified weighting scheme that is tailored to the specific research question is essential when specifying informative priors. To avoid arbitrary and subjective decisions, expert knowledge can inform this process (Bolsinova et al, 2017;van de Schoot et al, 2018;Veen et al, 2020). Expert knowledge as input for prior distributions has been previously used to estimate the size of parameters for which no data was available (e.g., Hald et al, 2016) or to complement existing data (e.g., van de Schoot et al, 2018).…”
Section: Weighting Previous Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have identified the negative impact of maternal depressive symptoms on different childhood outcomes, including internalizing and externalizing behavior problems (Ahun et al, 2018;Van Doorn et al, 2016). This association will be highlighted below, with empirical studies and scientific literature reviews, with emphasis on the influence of family interactions on the behavioral outcomes of school-age children, the focus of the present study.…”
mentioning
confidence: 92%